Empowering Micro-Businesses: Unveiling the Catalysts behind Social Media Integration in Indonesia - Adisthy Shabrina Nurqamarani; Sarah Fadilla; Agus Priyanto (TIJAB (The International Journal of Applied Business))
Background: An enormous number of micro-businesses in Indonesia have not joined the digital platforms, despite the evident benefits associated with making this transition. One viable avenue for initiating digitalization is through leveraging social media, characterized by its cost-effectiveness and expansive reach to consumers